Bacterial Biofilm And Role In The Pathogenesis Of Disease - Hussein Neamah, Bent Alhuda; Hussien Almousawi, Alia; Haider Aldujaili , Hadeel; Mohammed Chessab, Roaa (Medical Science Journal for Advance Research, 2022)
Background: Bacterial biofilms may play a role in pathogenesis which has led to increased focus on identifying diseases that may be associated with biofilms. Chronic biofilm infections are usually chronic in nature, as the bacteria that live in biofilms can be resilient to both the immune system and antibiotics and other treatments. Current knowledge of how biofilms contribute to disease pathogenesis suggests a number of different mechanisms. This extends from biofilms being merely a reservoir of pathogenic bacteria, to playing a more active role, for example, by contributing to inflammation. This knowledge is important for developing effective treatment strategies for such infections.